1990
DOI: 10.1007/bf01437534
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid effects in rotating helium clusters

Abstract: We study the response of Bose 4He clusters to an external field corresponding to a rotation with frequency co. An explicit form for the normal (nonsuperfluid) fraction of the system as a function of the temperature T and of the mass number N of the cluster is obtained under the assumption that only surface modes are thermally excited. The critical behaviour of 4He clusters at high rotational frequencies is also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Another salient feature of this work was that about 60 4 He atoms were enough to provide a superfluid environment for the OCS dopant. This observation is consistent with the theoretical predictions mentioned above [24]. To clarify this point, the authors also measured the OCS IR spectra doped in mixed 3 He/ 4 He droplets and controlled the number of 4 He atoms.…”
Section: Molecular-scale Superfluidity Versus Molecular Superfluidssupporting
confidence: 88%
See 1 more Smart Citation
“…Another salient feature of this work was that about 60 4 He atoms were enough to provide a superfluid environment for the OCS dopant. This observation is consistent with the theoretical predictions mentioned above [24]. To clarify this point, the authors also measured the OCS IR spectra doped in mixed 3 He/ 4 He droplets and controlled the number of 4 He atoms.…”
Section: Molecular-scale Superfluidity Versus Molecular Superfluidssupporting
confidence: 88%
“…The superfluidity of nano-scale He systems was first suggested by Lewart et al, who carried out variational Monte Carlo simulation for He clusters containing 20 to 240 atoms [21]. Based on the results of Feynmann path-integral Monte Carlo (PIMC) [22] simulations and other theoretical arguments, Sindzingre et al [23] and Pitaevskii and Stringari [24] concluded that the pure 4 He cluster with only 64 atoms demonstrated superfluidity through weak anomalies in heat capacity and reduced effective moment of inertia. The first microscopic Andronikashvili experiment can be traced back to the high-resolution infrared (IR) spectroscopy of an SF 6 molecule doped inside a liquid helium droplet consisting of about 4000 atoms.…”
Section: Molecular-scale Superfluidity Versus Molecular Superfluidsmentioning
confidence: 99%
“…First, specific cluster size effects, 4 involving self-selection and existence of ''magic numbers'' for moderately sized clusters, manifest an irregular variation of structure and energetics, which is not amenable to size scaling. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Landmark examples involve ( 4 He) N (Nу2) and ( 3 He) N (N у25) quantum clusters, which exhibit large zero-point energy motion, being the only clusters ͑and bulk materials͒ which are liquid and correspond to floppy nonrigid structures down to Tϭ0. [8][9][10] Third, nuclear adiabatic dynamics of clusters manifests new collective excitations, e.g., bulk compression modes, 5,6 and exhibits novel fragmentation patterns, such as cluster fission 11,12 and Coulomb explosion, 13,14 which are unique for finite systems and do not have an analogue in the dynamics of the corresponding bulk matter.…”
Section: Prologuementioning
confidence: 99%
“…15,16 Notable recent developments in the realm of lowtemperature large, finite, quantum systems pertain to the exploration of homonuclear molecular clusters ͑aggregates or nanodroplets͒, where the nuclear dynamics is dominated by quantum effects and by permutational symmetry. 31,33,48 Some of the features of the finite ( 4 He) N boson systems 17,30,33,[49][50][51][52][53][54][55] are as follows. 17-19,34 -46 These clusters manifest boson ͑for 4 He) or fermion ͑for 3 He) permutational symmetry.…”
Section: Prologuementioning
confidence: 99%
See 1 more Smart Citation